A Novel Jumbo Phage PhiMa05 Inhibits Harmful Microcystis sp. - Naknaen, Ampapan; Suttinun, Oramas; Surachat, Komwit; Khan, Eakalak; Pomwised, Rattanaruji (Frontiers in Microbiology, 2021)
Microcystis poses a concern because of its potential contribution to eutrophication and production of microcystins (MCs). Phage treatment has been proposed as a novel biocontrol method for Microcystis. Here, we isolated a lytic cyanophage named PhiMa05 with high efficiency against MCs-producing Microcystis strains. Its burst size was large, with approximately 127 phage particles/infected cell, a short latent period (1 day), and high stability to broad salinity, pH and temperature ranges. The PhiMa05 structure was composed of an icosahedral capsid (100 nm) and tail (120 nm), suggesting that the PhiMa05 belongs to the Myoviridae family. PhiMa05 inhibited both planktonic and aggregated forms of Microcystis in a concentration-dependent manner. The lysis of Microcystis resulted in a significant reduction of total MCs compared to the uninfected cells. A genome analysis revealed that PhiMa05 is a double-stranded DNA virus with a 273,876 bp genome, considered a jumbo phage. Out of 254 predicted open reading frames (ORFs), only 54 ORFs were assigned as putative functional proteins. These putative proteins are associated with DNA metabolisms, structural proteins, host lysis and auxiliary metabolic genes (AMGs), while no lysogenic, toxin and antibiotic resistance genes were observed in the genome. The AMGs harbored in the phage genome are known to be involved in energy metabolism (photosynthesis and tricarboxylic acid cycle) and nucleotide biosynthesis genes. Their functions suggested boosting and redirecting host metabolism during viral infection. Comparative genome analysis with other phages in the database indicated that PhiMa05 is unique. Our study highlights the characteristics and genome analysis of a novel jumbo phage, PhiMa05. PhiMa05 is a potential phage for controlling Microcystis bloom and minimizing MC occurrence.